2016
DOI: 10.1002/pc.23953
|View full text |Cite
|
Sign up to set email alerts
|

Effect of annealing at room temperature on the surface resistivity of elastomer/multiwalled carbon nanotube nanocomposites

Abstract: In this study, thermoplastic polyurethane (TPU) and ethylene propylene diene terpolymer (EPDM) were meltmixed with multi walled carbon nanotube (MWCNT), respectively. The change in the surface resistivity of the nanocomposites during annealing at room temperature was examined. The surface resistivity of TPU/MWCNT nanocomposites with 3 and 5 phr MWCNT and uncrosslinked EPDM/MWCNT nanocomposites with 4 and 6 phr MWCNT significantly increases with increasing annealing time at room temperature. To delay the increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…The above results proved that appropriate amount of nanoparticles has the expected strengthening/toughening effect on polymer materials. [23][24][25][26][27] From Figure 6A, it can be found that, as the size of SSSiO 2 particles decreased, the tensile strength and Young's modulus of TPUU/SSSiO 2 nanocomposites gradually increased, while the elongation at break gradually decreased, as also found in our study on TPUU/TiO 2 nanocomposites. 27 For example, the tensile strength and Young's modulus of the TPUU/SiO 2 nanocomposite increased from 55.3 and 695 to 75.5 and 802 MPa, respectively, while the elongation at break decreased from 760.3% to 584.5%, when the particle size decreased from 225 to 25 nm.…”
Section: Influence Of Size and Morphology Of Modified Sio 2 Nanoparti...supporting
confidence: 66%
See 2 more Smart Citations
“…The above results proved that appropriate amount of nanoparticles has the expected strengthening/toughening effect on polymer materials. [23][24][25][26][27] From Figure 6A, it can be found that, as the size of SSSiO 2 particles decreased, the tensile strength and Young's modulus of TPUU/SSSiO 2 nanocomposites gradually increased, while the elongation at break gradually decreased, as also found in our study on TPUU/TiO 2 nanocomposites. 27 For example, the tensile strength and Young's modulus of the TPUU/SiO 2 nanocomposite increased from 55.3 and 695 to 75.5 and 802 MPa, respectively, while the elongation at break decreased from 760.3% to 584.5%, when the particle size decreased from 225 to 25 nm.…”
Section: Influence Of Size and Morphology Of Modified Sio 2 Nanoparti...supporting
confidence: 66%
“…How to further enhance its performance is the goal that people have been pursuing, and the modification of TPU with nanoparticles has become a research hotspot in the field of TPU in recent years. [1][2][3][4][5][6][7][8][9][10] Among them, SiO 2 nanoparticles have also been widely used in the modification of TPU, [11][12][13][14][15][16][17][18][19][20][21][22][23][24] because of their excellent characteristics such as good thermal stability, high insulation, acid and alkali corrosion resistance, 25 and so forth. In addition, indeed the thermal and mechanical properties of TPU have been improved to varying degrees.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymer nanocomposites are a class of hybrid materials, which have generated a great interest in research and industry, due to their potentially novel properties, which are not existent in other materials . They have found many applications in a wide range of industries, such as automotive, civil construction, sport and aerospace in recent years.…”
Section: Introductionmentioning
confidence: 99%